REVISI PENGGUNAAN PUZZLE SEBAGAI MEDIA EVALUASI PENGUASAAN MUFRODAT - Maulida Azzahra; Suparmanto Suparmanto; Nanda Najwa Habibila; Nita Ernianti; Tatia Syarifatunnaja; Intan Nurul Hayati Aulia (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2026)
This study employs the Classroom Action Research (CAR) method, comprising the stages of planning, implementation, observation, and reflection. Puzzle media were used as an evaluation tool to assist students in understanding and retaining Arabic vocabulary through group activities. The results indicate that the use of puzzle media can enhance student engagement, motivation, and comprehension regarding Arabic vocabulary learning. Based on the evaluation results, 70% of the students (23 out of 33) achieved learning mastery, while 30% (10 students) did not. Students appeared more interested in participating in evaluation activities, more active in discussions, better able to collaborate on assembling puzzles, and more confident in providing answers. Furthermore, the use of puzzle-based media made the evaluation process interactive rather than monotonous, thereby boosting student learning motivation. Puzzle media proved effective as a tool for evaluating Arabic vocabulary learning.